PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-TALK-WRITE DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN KETERAMPILAN MENYELESAIKAN SOAL CERITA MATEMATIKA DI KELAS IV. - ALVIYANI, NOVI NUR (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract : The Use of Cooperative Learning Model Type Think-Talk-Write (TTW) with Concret Media in Improving Mathematics Story Problem Solving Skills for the Fourth Grade Studet of Elementary School. This research aims to improve the skills of solving Mathematics story problems at the fourth grade student of elementary school. The subjects were fourth grade students of elementary school totaling 27 students. Class Action Research was conducted in three cycles. Each cycle there were two meetings that consist of planning, action, observation, and reflection. Data collection techniques used testing, observation and interviews. The validity of data used triangulation techniques and triangulation of data sources. Data analysis applied the analysis of qualitative data and quantitative data. The results showed the use of cooperative models type TTW with concret media can improve mathematic problem solving skills for fourth grade student of elementary school. Keywords: Cooperative, Think-Talk-Write ,Concret Media, Story Problem Solving Abstrak : Penggunaaan Model Pembelajaran Kooperatif Tipe Think-Talk-Write dengan Media Benda Konkret dalam Peningkatan Keterampilan Menyelesaikan Soal Cerita Matematika di Kelas IV. Penelitian ini bertujuan meningkatkan keterampilan menyelesaikan soal cerita siswa kelas IV SD. Subjek penelitian ini siswa kelas IV SDN 5 Kebumen sejumlah 27 siswa. Penelitian Tindakan Kelas ini dilaksanakan dalam tiga siklus. Setiap siklus terdapat dua pertemuan terdiri dari tahap perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Teknik pengumpulan data dengan tes, observasi dan wawancara.. Validitas data menggunakan triangulasi data dan sumber. Analisis data dilakukan melalui analisis data kualitatif dan kuantitatif. Hasil penelitian menunjukkan penggunaan model kooperatif tipe TTW dengan media benda konkret dapat meningkatkan keterampilan menyelesaikan soal cerita di kelas IV SD. Kata Kunci: Kooperatif, Think-Talk-Write, Benda Konkret, Soal Cerita